FDI, Market Power, and Markups : Evidence from Vietnam - Li, Yue; Kuo, Ryan; Pinzon Latorre, Mauricio; Albertson, Mark (World Bank, Washington, DC, 2022)
To date, the impact of foreign direct investment on market power and consumer welfare in developing countries has been relatively understudied. Utilizing a firm survey dataset from Vietnam, this paper first calculates firm-level markups for manufacturing firms and then analyzes the impact of foreign direct investment and foreign ownership on firm markups. Overall, the findings show that increases in the presence of foreign firms in a given industry are associated with decreases in markups in that industry, despite foreign firms individually charging higher markups on average than their domestic competitors. The findings further show that while the markups of both foreign- and domestic-owned private firms tend to decrease with greater foreign direct investment, state-owned enterprises may be relatively insulated from foreign direct investment driven competitive pressures. These results are robust to the inclusion or exclusion of potential outliers and the potential non-random selection of firms acquired by foreign investors.